2023
DOI: 10.1111/1346-8138.16769
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic spectrum and therapeutic efficiency in teledermatology–Results of the largest cohort study to date

Abstract: Timely and comprehensive dermatological care is a major challenge. Digitized medical consultation offers a possibility to overcome this problem. Here, we studied the diagnostic spectrum and treatment success in teledermatology in the largest cohort to date. Over 12 months, 21 725 individuals received a diagnosis and therapeutic advice using the asynchronous image‐text method. In the context of quality management, 1802 individuals (~10%) of both sexes with a mean age of 33.7 years (SD 15.36) received a follow‐u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
(37 reference statements)
1
0
0
Order By: Relevance
“…In summary, the S&F application showed good feasibility, satisfaction, and acceptability while improving patients' health status. Similar to our results (85.1% solved requests), Lindemann et al 3 found therapeutic efficiency in 83.3% of patients, whereas Sondermann et al 4 stated that a diagnosis was possible in 90.3% of cases. Concerning the latter, 35.7% of patients were still recommended to see a physician in-person (21.3% in our study) and only 46.9% of patients received a therapy recommendation (71.0% in our study).…”
supporting
confidence: 91%
“…In summary, the S&F application showed good feasibility, satisfaction, and acceptability while improving patients' health status. Similar to our results (85.1% solved requests), Lindemann et al 3 found therapeutic efficiency in 83.3% of patients, whereas Sondermann et al 4 stated that a diagnosis was possible in 90.3% of cases. Concerning the latter, 35.7% of patients were still recommended to see a physician in-person (21.3% in our study) and only 46.9% of patients received a therapy recommendation (71.0% in our study).…”
supporting
confidence: 91%